Peran Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan Di MAN 1 Kota Makassar - Samiuddin; Andi Bunyamin; Andi Darmawangsa (Journal of Gurutta Education, 2022)
Quality education is expected to form quality Indonesian people who believe and fear God Almighty and carry out religious orders according to what they adhere to. One proof of the government's seriousness in developing the quality of educational institutions is stated in government regulation no. 57 of 2021. The purpose of this study is to determine the extent of the Madrasah Head's strategy in improving the quality of education at MAN 1, Makassar City. The research method used is a qualitative approach. Sources of data were obtained from the head of the madrasa, vice principal, and staff of MAN 1 Makassar City. The results showed that the Head of Madrasah MAN 1, Makassar City, improved the quality of education by implementing bartering, building, binding, and bonding strategies. The Head of Madrasah MAN 1 Makassar City makes efforts by instilling the attitude of the heart of education (learning by heart), supervising, applying discipline and building cooperation with various educational stakeholders